Ultrasonographic findings in wrists and hands of patients with clinical suspicion of early phase rheumatoid arthritis (Boletin Médico de Postgrado, 2020)
Rheumatoid Arthritis (RA) is a chronic and autoimmune disease whose first year of clinical manifestations is considered the early phase of the disease according to the American College of Rheumatology. With the aim of describing the ultrasonographic findings in the wrists and hands of patients with clinical suspicion of early phase RA referred to the Rheumatology Service of the Hospital Central Universitario Dr. Antonio Maria Pineda during the period June-August 2018, a cross-sectional descriptive study was conducted evaluating 126 joints of 21 patients according to the modified scale of the OMERACT. Patients had an average age of 51.4 ± 11.1 years and the most affected age groups was the 41-50 years and 51-60 years. Predominance of female sex (85.71%) as well as an average of 5.2 ± 2.8 months of time of symptoms onset was observed. The main alterations observed were synovial effusion (54.7%), synovial thickening (28.5%), tenosynovitis in extensor tendons (28.5%), bone erosions (11.1%) and tenosynovitis in flexor tendons (9.52%). The radiocarpal joints were the most affected showing grade 1 synovial hypertrophy and synovitis in 12.7% and 7.9% of joints, respectively; grade 1 and 2 synovial effusion was observed in 15% of joints and small bone erosions in 7.9%. For the second metacarpophalangeal joint, grade I synovial hypertrophy was found in 8.7% of joints, synovitis in 6.3%, synovial effusion in 13.4% and medium-sized bone erosions in 1.5%; in 0.79% of the proximal interphalangeal joints grade I synovial effusion was observed. Tenosynovitis grade 1 was observed in 25.4% of extensor tendons and 7.9% flexors. The use of ultrasonography should be encouraged as a complementary tool for the diagnosis of RA, avoiding unnecessary expenses and delay in treatment.
Keywords: rheumatoid arthritis; wrist joint; hand joints; ultrasonography